2002
DOI: 10.1038/sj.hdy.6800114
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure in a Mediterranean pine (Pinus pinaster Ait.): a comparison of allozyme markers and quantitative traits

Abstract: F-statistics were employed to analyse quantitative and allozyme variation among 19 native populations of maritime pine (Pinus pinaster Ait.). Fourteen polymorphic allozyme loci were used to provide an empirical basis for constructing a null hypothesis to test natural selection as a determinant of quantitative evolution in stem form, total height growth and survival at 30 years old. Hidden biases, that may result in a difference between quantitative (Q ST ) and allozyme (F ST ) differentiation which are not bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
2
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 40 publications
6
67
2
7
Order By: Relevance
“…A high level of phenotypic plasticity for growth and drought tolerance has been reported in several studies (Chambel, 2007;Hopkins and Butcher, 1993;Zas et al, 2004), with Atlantic provenances displaying lower survival under severe water deficits (Alía et al, 1995) or frost stress (Hopkins and Butcher, 1993). Differences in stem form have also been found among populations, mainly explained by differences in competition for light and resistance to snow and wind, with highland populations displaying a better form (González-Martínez et al, 2002;Sierra de Grado et al, 1997).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…A high level of phenotypic plasticity for growth and drought tolerance has been reported in several studies (Chambel, 2007;Hopkins and Butcher, 1993;Zas et al, 2004), with Atlantic provenances displaying lower survival under severe water deficits (Alía et al, 1995) or frost stress (Hopkins and Butcher, 1993). Differences in stem form have also been found among populations, mainly explained by differences in competition for light and resistance to snow and wind, with highland populations displaying a better form (González-Martínez et al, 2002;Sierra de Grado et al, 1997).…”
Section: Introductionmentioning
confidence: 94%
“…At the species range, variability of growth and stem form is weakly related to the structure found using Article published by EDP Sciences different molecular markers (González-Martínez et al, 2002;, showing 3 main groups: Western (Atlantic), Eastern (Mediterranean) and Moroccan. At present, new insights on the association of drought stress candidate genes to local adaptation patterns are revealing different groups (Eveno et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altitudinal and longitudinal variations have also been shown by Dangasuk and Panetsos (2004) on some morphological traits of the species on Crete Island, Greece. Gonzalez-Martinez et al, (2002) indicate that environmental heterogeneity and genotypeby-environment interactions seem to have a major role in quantitative differentiation when gene flow is high. Also, they suggested that some ecological factors (rainfall, temperature, altitude, soil types) are the main determinants of the interaction in maritime pine in Spain.…”
Section: Comparison Of the Populationsmentioning
confidence: 99%
“…Common garden material can provide valuable information to explain genetic differentiation and processes of adaptation of trees to different environments which can then be compared to molecular genetic information (Gonzalez-Martinez et al, 2002;Whitlock, 2008). Specific study objectives are (i) to use highly polymorphic RAPD loci to determine levels of genetic variation and population genetic structure along altitudinal gradients; (ii) to compare molecular and quantitative data related to genetic diversity and differentiation estimates on the same populations and families; and finally, (iii) to interpret the results in view of forest management practices, conservation and genetic improvement of the species.…”
Section: Introductionmentioning
confidence: 99%